Artisanal fisheries in urban reservoirs: a case study from Brazil (Billings Reservoir, São Paulo Metropolitan Region) - Minte-Vera, C. V.; Petrere, M. (Blackwell Science, 2000)
Billings Reservoir is an urban reservoir located in the São Paulo Metropolitan Region. Tt supports 101 active artisanal fishermen. To describe this fishery, landings were recorded daily between February 1996 and January 1997 at Colonia (23 degrees 50' 57 S; 46 degrees 40' 02 W). In every landing, a data collector recorded catch, effort, fishing gears and fishing grounds. A total of 147 593 kg of fish were recorded in 3515 fishing trips. The exotic Nile tilapia, Oreochromis niloticus (L.), was the main species exploited (81.4% of the annual catches). Five other species were also targeted: the characid Astyanax eigenmaniorum (Cope) (13.0% of the annual catches); the erythrinid Hoplias aff malabaricus (Block) (2.1%); the exotic cyprinid Cyprinus carpio L. (Campos & Fernandez-Yepez) (2.4%); the curimatid Cyphocharax modestus L. (1.1%); and the pimelodid Rhamdia sp. (0.1%). Two main groups of fishermen were discriminated using Principal Components Analysis; these were associated with the type of fishing gear and fishing strategies, i.e. those who exploited Nile tilapia with cast nets and beating gill nets, and those who exploited other species with set gill nets. Management and maintenance of this fishery should consider the positive top-down effects that Nile tilapia could have in controlling eutrophication and also the social benefits.
Keywords: artisanal fisheries; catch; fishing effort; fishing strategies; Oreochromic niloticus; urban fisheries